Assessing the predictability of IDH mutation and MGMT methylation status in glioma patients using relaxation-compensated multipool CEST MRI at 7.0 T. Issue 12 (4th May 2018) - Paech, Daniel; Windschuh, Johannes; Oberhollenzer, Johanna; Dreher, Constantin; Sahm, Felix; Meissner, Jan-Eric; Goerke, Steffen; Schuenke, Patrick; Zaiss, Moritz; Regnery, Sebastian; Bickelhaupt, Sebastian; Bäumer, Philipp; et al.
Abstract: Background: Early identification of prognostic superior characteristics in glioma patients such as isocitrate dehydrogenase ( IDH ) mutation and O 6 -methylguanine-DNA-methyltransferase ( MGMT ) promoter methylation status is of great clinical importance. The study purpose was to investigate the non-invasive predictability of IDH mutation status, MGMT promoter methylation, and differentiation of low-grade versus high-grade glioma (LGG vs HGG) in newly diagnosed patients employing relaxation-compensated multipool chemical exchange saturation transfer (CEST) MRI at 7.0 Tesla. Methods: Thirty-one patients with newly diagnosed glioma were included in this prospective study. CEST MRI was performed at a 7T whole-body scanner. Nuclear Overhauser effect (NOE) and isolated amide proton transfer (APT; downfield NOE-suppressed APT = dns-APT) CEST signals (mean value and 90 th signal percentile) were quantitatively investigated in the whole tumor area with regard to predictability of IDH mutation, MGMT promoter methylation status, and differentiation of LGG versus HGG. Statistics were performed using receiver operating characteristic (ROC) and area under the curve (AUC) analysis. Results were compared with advanced MRI methods (apparent diffusion coefficient and relative cerebral blood volume ROC/AUC analysis) obtained at 3T. Results: dns-APT CEST yielded highest AUCs in IDH mutation status prediction (dns-APTmean = 91.84%, P < 0.01; dns-APT90 = 97.96%, P < 0.001). Furthermore, dns-APT metrics enabled significant differentiation of LGG versus HGG (AUC: dns-APTmean = 0.78, P < 0.05; dns-APT90 = 0.83, P < 0.05). There was no significant difference regarding MGMT promoter methylation status at any contrast ( P > 0.05). Conclusions: Relaxation-compensated multipool CEST MRI, particularly dns-APT imaging, enabled prediction of IDH mutation status and differentiation of LGG versus HGG and should therefore be considered as a non-invasive MR biomarker in the diagnostic workup.